Magnetic Abrasive Finishing’s Potential: Challenges & Opportunities - Munjal, Nitish (Journal of Advanced Research in Instrumentation and Control Engineering, 2024)
The Magnetic Abrasive Finishing (MAF) technique has a potential for achieving high-quality surface finishing by offering a self-sharpening and adaptable approach to attaining surface finishes at the nanometer level. This review paper provides a thorough examination of the current state, feasibility, challenges, opportunities, and future directions of MAF. It briefs on the fundamental principles of MAF, including magnetic forces, abrasive particles, and process parameters. Furthermore, this study and this article brief the hybrid methods of magnetic abrasive finishing (MAF), including electrolytic magnetic abrasive finishing (EMAF) and vibration-assisted magnetic abrasive finishing (VMAF). The prime advantages of MAF include the ability to precisely machine delicate materials, control finishing pressures, and achieve exceptional surface quality. The article also highlights the constraints, such as the intricacy of achieving complicated forms, limited efficiency, and limited applicability to ferromagnetic materials. This paper examines how process factors affect the quality and the rate of material removal. It explores the possibilities of MAF in industries such as aerospace, semiconductors, and medical devices, where accurate surface finishing is crucial. The review emphasizes the need for further research on optimizing process parameters, developing hybrid MAF processes, and exploring new applications. Understanding the interplay between parameters, finishing mechanisms, and hybrid techniques can unlock MAF’s full potential and expand its applications in various industries. This comprehensive review aims to guide the development of MAF technologyand its applications.